Design of E. Coli Systems as Iron Waste Binders for Wastewater Treatment using Synthetic Biology Approach - Indah Oktaviani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2018)
The development of recombinant DNA technology and the emerging field of synthetic biology have open up a more advanced era of biotechnology. The discoveries are developed to solve the existing problems in the community.The presence of the iGEM competition initiated by the iGEM Foundation since 2003 adding up new data and a new discovery that is constantly being improved upon, so that peoples’ interest and concern with synthetic biology in the world are increasing every year, including in Indonesia.This paper discusses the idea of design to develop an expression system with a synthetic biology approach using standard parts listed on the iGEM website.The system design uses Escherichia coli as its chassis to have the capability as an iron waste bioaccumulator agent in the waters. This draft is expected to be one of the contributions for the future of the development of synthetic biology ideas, research, and applications in handling environmental problems in Indonesia.